A license to kode. - Neville-Neil, George (New York ACM, 2007)
A koder with attitude, KV answers your questions. Miss Manners he ain't.
Keywords: Software; Software engineering; General Literature; Computing Milieux; Management of Computing and Information Systems; Design; Management